تحليل الوضع الراهن لإنتاج واستهلاك لحوم الأغنام في ليبيا مع تقييم الفجوة الغذائية ونصيب الفرد - د.الهام جمعة البقي (Aljameai, 2026)
المستخلص:تلعب لحوم الأغنام دورًا أساسيًا في تأمين البروتين الحيواني وتعزيز الأمن الغذائي في ليبيا. وتهدف هذه الدراسة إلى تحليل إنتاج واستهلاك لحوم الأغنام خلال الفترة 2018–2023، مع التركيز على الفجوة الغذائية ونصيب الفرد، وتحديد العوامل المؤثرة على الإنتاج المحلي، وتقييم مساهمة الواردات في تلبية الطلب الوطني. واتبعت الدراسة المنهج الوصفي التحليلي باستخدام البيانات الرسمية الوطنية والدولية، بالإضافة إلى الدراسات العربية ذات الصلة. أظهرت النتائج أن الإنتاج المحلي ظل مستقرًا عند نحو 40–43 ألف طن سنويًا، بينما ارتفع الاستهلاك تدريجيًا من 55 إلى 60 ألف طن، ما أدى إلى اتساع الفجوة الغذائية من 14 إلى 19 ألف طن. وبلغ نصيب الفرد من لحوم الأغنام حوالي 8–8.7 كجم/سنة، فيما انخفضت نسبة الأغنام ضمن إجمالي استهلاك اللحوم الحمراء، مما يعكس تغيرات في التركيبة الغذائية للسكان. وأوضحت الدراسة أن الإنتاج المحلي يتأثر بالموارد الطبيعية المحدودة، نظم التربية والتغذية التقليدية، ضعف البنية التحتية، محدودية الدعم الفني والمالي، وغياب سياسات وطنية واضحة. وتوصي الدراسة بوضع استراتيجيات لتعزيز الإنتاج المحلي عبر تحسين نظم التربية والتغذية، تقديم الدعم المالي والفني للمربين، تطوير البنية التحتية، وتشجيع اعتماد نظم إنتاج حديثة، بهدف تعزيز الأمن الغذائي الحيواني بشكل مستدام. Abstract:Sheep meat plays a crucial role in providing animal protein and enhancing food security in Libya. This study aims to analyze sheep meat production and consumption during 2018–2023, focusing on the food gap, per capita availability, and key factors affecting local production, as well as evaluating the contribution of imports to national demand. A descriptive-analytical approach was applied using official national and international data, supplemented by relevant Arabic studies. Results indicated that domestic production remained stable at approximately 40–43 thousand tons annually, while consumption gradually increased from 55 to 60 thousand tons, leading to a widening food gap from 14 to 19 thousand tons. Per capita availability of sheep meat was around 8–8.7 kg/year, while the share of sheep meat in total red meat consumption declined, reflecting changes in dietary patterns. Local production is influenced by limited natural resources, traditional husbandry and feeding systems, weak infrastructure, insufficient technical and financial support, and absence of clear national policies. The study recommends strategies to enhance domestic production through improving husbandry and feeding practices, providing technical and financial support to farmers, developing infrastructure, and promoting the adoption of modern production systems, aiming to strengthen sustainable animal food security